Tilawah Al-Qur’an Sebagai Terapi Psiko-Spiritual dalam Meningkatkan Kesehatan Mental Santri di Pondok Pesantren Darul Muttaqin Metro - Della Monica; Kuliyatun Kuliyatun; Heri Cahyono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Recitation of the Qur'an in Islamic boarding school education isn’t only understood as a ritual worship, but also as a religious practice that plays a big role in regulating emotions and fostering inner calm. In the daily life of students at Darul Muttaqin Islamic Boarding School, various pressures such as academic demands, memorization targets, homesickness, and social adjustment often generate psychological tension. This study explores how Qur’anic recitation functions as a form of psycho-spiritual therapy that supports students’ mental well-being. This study employed a qualitative descriptive approach with a field-based design. Information was obtained through in-depth interviews, participant observation, and documentation with fifteen students who regularly perform tilawah (Islamic recitation) and two female teachers. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings prove that tilawah assists students in managing their emotions, reducing anxiety, and cultivating spiritual tranquility. Students who consistently recite the Qur’an appear better equipped to cope with academic pressure and demonstrate patience, gratitude, and sincerity in their daily activities. These values serve as internal coping mechanisms that strengthen their psychological resilience. Overall, the study affirms that Qur’anic recitation can serve as an effective psycho-spiritual therapeutic model for maintaining students’ mental health in the pesantren environment.